DAMPAK APLIKASI INSEKTISIDA PERMETRIN TERHADAP HAMA PENGISAP BIJAIJ HELOPELTIS SPP. (HEMIPTERA: MIRIDAE) DAN ARTROPODA NON-TARGET PADA PERTANAMAN KAKAO (THEOBROMA CACAO L.) - Hasibuan, Rosma; Swibawa, I Gede; Wibowo, Lestari; Pramono, Sudi; Hariri, Agus M (JURNAL HAMA DAN PENYAKIT TUMBUHAN TROPIKA, 2004)
Impact of Permethrin-Insecticide Application on Mirid Pest of Cocoa Helopeltis spp. (Hemiptera: Miridae) and on Non-target  Arthropods in Cocoa Plantations (Theobroma cacao L.). Cocoa mirid bugs, Helopeltis spp., (Hemiptera: Miridae) are the most important pest of cocoa in Indonesia. A field study was conducted to investigate the effect of permethrin on cocoa mirids and non-target arthropods at a cocoa plantation in specific place. A randomized complete block design was used in which each of four blocks consisted of 5 treatments (4 concentrations of permethrin; 50; 100; 200; and 250 ppm and control). The results indicated that the application of permethrin significantly increased the cocoa mirids mortaliiy throughout all sprayed cocoa trees (up to 100% 72 h after application). Even at 1 h after application, the percentage of Cocoa mirids mortality 29.2% - 53.9%) on cocoa trees sprayed with permethrin at concentrations of 50 - 250 ppm was significantly higher than that on control plant (3.6%). At 72 h after treatments, application of permethrin at concentrations of 200 and 250 ppm caused a complete kill (mortalty of 100%) in the test mirids. Meanwhile, ground cloths caught at least 22 fanilies of abore-ground arthropods that were found killed by permethrin applications. Moreover, the number of non-target arthropods killed by permethrin at concentrations of 100 - 250 ppm (27.3 - 85.3 individuals/ground cloth) were signifcantly higher than that on control trees. These results demonstrated that despite high efficacy of permethrin in controlling of cocoa mirids (Hetopeltis spp.), its application also had adverse effects on non-target arthropods incocoa plantations.